2012
DOI: 10.1097/mao.0b013e318241c0bf
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of More Than 1,000 Implanted Percutaneous Bone Conduction Devices

Abstract: Children and patients with mental retardation are the most vulnerable to soft tissue reactions and implant losses. Additional and more frequent care needs to be given during outpatient consultations. Because loading as early as 3 to 5 weeks did not negatively affect skin reactions or implant survival, full BCD installation can occur earlier without risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
4
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 31 publications
10
134
4
5
Order By: Relevance
“…The greatest disadvantage is the experience of still not being able to participate in group conversations, especially in a noisy environment. Although adverse skin reactions with a BCI have been mentioned in several previous studies (28), none of the patients in the current study reported complications with the BCI screw or the abutment as a main disadvantage of the hearing system. However, the focus of the study was not the surgical aspects of the BCI.…”
Section: Discussioncontrasting
confidence: 46%
“…The greatest disadvantage is the experience of still not being able to participate in group conversations, especially in a noisy environment. Although adverse skin reactions with a BCI have been mentioned in several previous studies (28), none of the patients in the current study reported complications with the BCI screw or the abutment as a main disadvantage of the hearing system. However, the focus of the study was not the surgical aspects of the BCI.…”
Section: Discussioncontrasting
confidence: 46%
“…There appears to be little difference in the risk of osseointegration failure for those patients loaded at less than 6 weeks or more than 12 weeks, or even at 4 weeks post-operatively. [8][9][10] Recent advances in fixture technology include a wider diameter fixture to increase the bone-fixture contact area and novel fixture coatings to speed up osseointegration. 11 Both of these may permit earlier loading than has traditionally been performed.…”
Section: Introductionmentioning
confidence: 99%
“…This is much less compared to what is described in literature for previous generation implants in children [7,[9][10][11][12]. The reduced frequency of implant loss for the new generation implant was expected based on the results of implant stability studies in adult patients, seen in the clinical trial by Dun et al [2].…”
Section: Comparison With Other Studiesmentioning
confidence: 85%
“…This is the case in most studies reporting on clinical outcomes, since children are usually not included in clinical trials and smaller numbers of patients are available. However, clinical outcome evaluation in children is highly relevant, as previous series showed a significantly higher incidence of complications in children compared to adults (implant loss approximately 15%), all implanted with the previous generation implants [7]. The aim of the current study was to verify the subjective increase of soft tissue problems in our pediatric BAHI population.…”
Section: Introductionmentioning
confidence: 95%